Synthesis of Triacetin Catalyzed by Activated Natural Zeolite Under Microwave Irradiation (Universitas Negeri Semarang, 2019)
Esterification of glycerol with acetic acid under microwave irradiation in the presence of activated natural zeolite was investigated. Natural zeolite was collected from Ujung Pancu (Aceh Besar) and chemically activated with hydrochloric acid. The reaction was carried out in a stirred glass flask reactor placed inside microwave oven. Experimental variables include microwave transmission time, molar ratio of glycerol to acetic acid, and catalyst loading. XRD profile of activated zeolite showed an increase of Si/Al ratio to 6.042 and the crystallinity decreased slightly by 12.23%, mainly due to dealumination during chemical treatment. Qualitative analysis by FTIR shows that the reaction product obtained by microwave heating contains ester group (triacetin) at wavelength 1706.669 cm-1, while the quantitative analysis by acidi-alkalimetry titration indicates the highest glycerol conversion of 93.033% at the reaction condition of the molar ratio of 1:9, catalyst loading of 3%, and microwave transmission of 10 minutes. The present work suggests that microwave can be utilized as efficient heating technique in esterification of glycerol to triacetin.